把多项式(3a-4b)(7a-8b)-(11a-12b)(7a-8b)因式分解的结果是A.8(7a-8b)(a-b)B.2(7a-8b)²C.8(7a-8b)(b-a)D.-2(7a-8b)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 09:58:27
把多项式(3a-4b)(7a-8b)-(11a-12b)(7a-8b)因式分解的结果是A.8(7a-8b)(a-b)B.2(7a-8b)²C.8(7a-8b)(b-a)D.-2(7a-8b)
把多项式(3a-4b)(7a-8b)-(11a-12b)(7a-8b)因式分解的结果是
A.8(7a-8b)(a-b)
B.2(7a-8b)²
C.8(7a-8b)(b-a)
D.-2(7a-8b)
把多项式(3a-4b)(7a-8b)-(11a-12b)(7a-8b)因式分解的结果是A.8(7a-8b)(a-b)B.2(7a-8b)²C.8(7a-8b)(b-a)D.-2(7a-8b)
(3a-4b)(7a-8b)-(11a-12b)(7a-8b)
=(7a-8b)(3a-4b-11a+12b)
=(7a-8b)(-8a+8b)
=8(7a-8b)(b-a)
选C
C
(3a-4b)(7a-8b)-(11a-12b)(7a-8b)
=(7a-8b)(a-4b-11a+12b)
=.8(7a-8b)(b-a)
(3a-4b)(7a-8b)-(11a-12b)(7a-8b)=(3a-11a-4b+12b)(7a-8b)=(-8a+8b)(7a-8b)=8(b-a)(7a-8b)
所以答案选C
c
(3a-4b)(7a-8b)-(11a-12b)(7a-8b)
=(7a-8b)(3a-4b-11a+12b)
=(7a-8b)(8b-8a)
=8(7a-8b)(b-a)
(3a-4b)(7a-8b)-(11a-12b)(7a-8b)
=(7a-8b)[(3a-4b)-(11a-12b)]
=(7a-8b)(-8a+8b)
=8(7a-8b)(b-a)
所以选C
(7a-8b)(3a-4d-11a+12b) =(7a-8b)(8b-8a) 8(7a-8b)(8b-8a)